Revealing the Angiopathy of Lacrimal Gland Lesion in Type 2 Diabetes - Xue, Junfa; Zhang, Bin; Dou, Shengqian; Zhou, Qingjun; Ding, Min; Zhou, Mingming; Wang, Huifeng; Dong, Yanling; Li, Dongfang; Xie, Lixin (Frontiers in Physiology, 2021)
For a better understanding of diabetic angiopathy (DA), the potential biomarkers in lacrimal DA, and its potential mechanism, we evaluated the morphological and hemodynamic alterations of lacrimal glands (LGs) in type 2 diabetes patients and healthy counterparts by color Doppler flow imaging (CDFI). We further established a type 2 diabetic mice model and performed HE, immunofluorescence staining of CD31, RNA-sequencing analysis, and CMap analysis. We found atrophy and ischemia in type 2 diabetes patients and mice models. Furthermore, we identified 846 differentially expressed genes (DEGs) between the T2DM and vehicle mice by RNA-seq. The Gene Ontology (GO) analysis indicated significant enrichment of immune system process, regulation of blood circulation, apoptotic, regulation of secretion, regulation of blood vessel diameter and so on. The molecular complex detection (MCODE) showed 17 genes were involved in the most significant module, and 6/17 genes were involved in vascular disorders. CytoHubba revealed the top 10 hub genes of DEGs, and four hub genes (App, F5, Fgg, Gas6) related to vascular regulation were identified repeatedly by MCODE and cytoHubba. GeneMANIA analysis demonstrated functions of the four hub genes above and their associated molecules were primarily related to the regulation of circulation and coagulation. Connectivity Map (CMap) analysis found several small molecular compounds to reverse the altered DEGs, including disulfiram, bumetanide, genistein and so on. Our outputs could empower the novel potential targets to treat lacrimal angiopathy, diabetes dry eye, and other diabetes-related diseases.